The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/geosciences9120513
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Modelled Reactions of CO2 and SO2 with Core from a Low Salinity Aquifer Overlying a Target CO2 Storage Complex

Abstract: CO 2 -induced reactions in low salinity aquifers overlying CO 2 storage sites are of interest to understand potential reactions or impacts in the possible case of a leak. Previous investigations of overlying aquifers in the context of CO 2 storage have focused on pure CO 2 streams, however captured industrial CO 2 streams may contain ancillary gases, including SO 2 , O 2 , NOx, H 2 S, N 2 , etc., some of which may be more reactive than CO 2 when dissolved in formation water. Eight drill cores from two wells in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Dong [31] applied TOGUHREACT to simulate the changes of formation pressure, fluid pH, ion content, mineral dissolution, precipitation, reservoir physical properties, and CO 2 storage, and studied the influence of CO 2 -water-rock interaction on reservoir properties. Pearce [32] experiment found that in sandstone rich in chlorite, when CO 2 reacts with low concentration SO 2 , rock porosity will not increase, but there is particle movement, which damages permeability. Ahmat [33] In order to better understand CO 2 -water-rock interaction, Different mineral compositions and fluid salinity were numerically simulated and experimentally analyzed.…”
Section: Supercritical Co 2 -Water-rock Reaction Experiments and Coup...mentioning
confidence: 99%
“…Dong [31] applied TOGUHREACT to simulate the changes of formation pressure, fluid pH, ion content, mineral dissolution, precipitation, reservoir physical properties, and CO 2 storage, and studied the influence of CO 2 -water-rock interaction on reservoir properties. Pearce [32] experiment found that in sandstone rich in chlorite, when CO 2 reacts with low concentration SO 2 , rock porosity will not increase, but there is particle movement, which damages permeability. Ahmat [33] In order to better understand CO 2 -water-rock interaction, Different mineral compositions and fluid salinity were numerically simulated and experimentally analyzed.…”
Section: Supercritical Co 2 -Water-rock Reaction Experiments and Coup...mentioning
confidence: 99%
“…The trace metal mobilization response to impure CO 2 injection is even less well known than that from pure CO 2 injection (Pearce et al, 2015a;Marcon and Kaszuba, 2015;Pearce et al, 2019d). Real potential or perceived public concerns for the risk of CO 2 and brine or formation water leakage into low-salinity aquifers has led to recent interest in the potential impacts on water quality (Lawter et al, 2016;Kharaka et al, 2018;Pearce et al, 2019c). Recent work includes the study of natural sites of CO 2 accumulation and CO 2 or brine leakage up faults, fractures, or old wellbores (Viswanathan et al, 2012); field studies of deep or shallow CO 2 injection sites (Zheng et al, 2009;Yang et al, 2013); experimental studies of mineral reactions from drill core resulting in metal mobilization (Shao et al, 2014;Golding et al, 2019;Shao et al, 2020); and transport or geochemical modeling studies to predict if leakage could be expected and if metal mobilization would be of sufficient magnitude to cause a risk or if metals are resequestered by adsorption and re-precipitation of minerals (Carroll et al, 2014;Zheng et al, 2016;Pearce et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%